2017
DOI: 10.3329/bjme.v8i2.33331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacology Written Question Papers of MBBS Professional Examinations

Abstract: This cross sectional descriptive study was conducted to observe the quality of Pharmacology professional written question papers of Bangladesh University of Professionals (BUP), University of Chittagong (CU), University of Dhaka (DU), Rajshahi University (RU) and Shahjalal University of Science & Technology (SUST).For this purpose total 82 SAQ papers of five universities dated from January 2007 to July 2015 were reviewed. Question papers were reviewed to find out the coverage of recall, understanding and probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
11
9
0
Order By: Relevance
“…But in this study we observed that highest percentage of questions are recall in all universities i.e 80 to 90 percent. This findings are similar to othrer observations 14,18 Understanding type of questions were only 5 percent, application type were 4 percent and problem solving questions only 2 percent.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…But in this study we observed that highest percentage of questions are recall in all universities i.e 80 to 90 percent. This findings are similar to othrer observations 14,18 Understanding type of questions were only 5 percent, application type were 4 percent and problem solving questions only 2 percent.…”
Section: Discussionsupporting
confidence: 78%
“…It was seen that different university under same curriculum prepare question for written examination in different format. In our country only one study 14 was found on focusing undergraduate pharmacology written question evaluation has been carried since 2002 curriculum. Therefore the present study was done with the aim to analyze the pharmacology written question (SAQ) held under different universities regarding content coverage, type of question and objectives of course.…”
Section: Introductionmentioning
confidence: 99%
“…30 Problem based questions are for students to assess their knowledge and understanding level through which they can solve problem in a novel situation. 31 Current research found that percentage of problem based question had reduced dramatically over the last 10 years and this finding was concurrent to previous two studies conducted in Bangladesh 24,26 although there is already identified need by pharmacology educators of the country to incorporate problem based questions in undergraduate written exams. 32 Regarding weightage of problem based questions, another point is significant difference (<0.00001) was observed among different universities in current study.…”
Section: Discussionsupporting
confidence: 61%
“…19, 20 Several studies were conducted in Bangladesh to evaluate pharmacology education (curriculum, textbooks and question papers) from different perspectives. 21, 22, 23, 24, 25, 26 In this backdrop, current study was conducted to evaluate pharmacology written question papers of last 10 years with the attempt to find out the weightage and trend of problem-solving questions in the written assessment system.…”
Section: Introductionmentioning
confidence: 99%
“…22 Seven public universities, Bangladesh University of Professionals textbooks and question papers through different perspectives. [23][24][25][26][27][28] In this background, current study was conducted to evaluate Pharmacology written question papers of different universities over last 10 years in the context of reflection of curricular objectives, content coverage and selective disease burdens.…”
Section: Introductionmentioning
confidence: 99%